Early experience of Sacubitril–Valsartan in heart failure with reduced ejection fraction in real‐world clinical setting - Charlotte Nordberg Backelin; Michael Fu; Charlotta Ljungman (ESC Heart Failure)
Abstract Aims Sacubitril/Valsartan (Sac/Val) was proven more effective than enalapril for symptomatic patients with heart failure (HF) with reduced ejection fraction (HFrEF). This study aimed to investigate eligibility, titration, and tolerability for Sac/Val in a real‐world clinical setting. Methods and results This retrospective cohort study consists of two parts. In Part 1 (eligibility study), all patients discharged from Sahlgrenska University Hospital due to HF were consecutively included during 1 year. Data from the patients' medical records were collected. Patients were adjudicated to be eligible based on European Society of Cardiology (ESC) criteria for angiotensin receptor neprilysin inhibitor (ARNI) with the exception of N‐terminal (NT)‐proBNP levels. Patients who received <50% of target dose angiotensin‐converting enzyme/angiotensin receptor blocker and otherwise fulfilled ESC criteria were adjudicated to be potentially eligible. In Part 2 (tolerability study), all patients receiving Sac/Val during the same period were included. Medical data regarding dose, titration, and adverse effects and events were registered. A total of 1355 patients (mean age 78 ± 13 years) were hospitalized for HF and 619 patients had an EF ≤40%. Twenty percent were eligible for initiation of ARNI, and additionally 8% were potentially eligible. In all 95 patients (mean age 65 ± 12 years) were initiated with Sac/Val, which correlates to 13%. The patients who were initiated were younger (65 years), more often had dilated cardiomyopathy (31%), more often were on guideline‐directed medical therapy, and had a higher frequency of cardiac resynchronization therapy and implantable cardioverter–defibrillator compared with the patients who did not receive Sac/Val. Of the initiated patients, 59% reached target dose of Sac/Val, and 15% discontinued due to adverse effects. The most common cause of discontinuation was benign gastrointestinal adverse effects, followed by elevated creatinine, malaise, and vertigo. Female gender [odds ratio (OR) 3.58; 95% CI 1.07–2.00; P = 0.038] and NT‐proBNP ≥ median level (OR 0.48; 95% CI 0.26–0.90; P = 0.021) was associated with termination of the medication. Conclusions Among HFrEF patients in this real‐world cohort, 20% were eligible for ARNI; however, only 13% received the treatment. Sac/Val was well tolerated, but 41% of the patients did not reach target dose. How this affects outcome is not known and needs further investigation.